Immune regulation and therapeutic application of T regulatory cells in liver diseases - Ajith, Ananya; Merimi, Makram; Arki, Mandana Kazem; Hossein-khannazer, Nikoo; Najar, Mehdi; Vosough, Massoud; Sokal, Etienne Marc; Najimi, Mustapha (Frontiers in Immunology, 2024)
CD4+ CD25+ FOXP3+ T regulatory cells (Tregs) are a subset of the immunomodulatory cell population that can inhibit both innate and adaptive immunity by various regulatory mechanisms. In hepatic microenvironment, proliferation, plasticity, migration, and function of Tregs are interrelated to the remaining immune cells and their secreted cytokines and chemokines. In normal conditions, Tregs protect the liver from inflammatory and auto-immune responses, while disruption of this crosstalk between Tregs and other immune cells may result in the progression of chronic liver diseases and the development of hepatic malignancy. In this review, we analyze the deviance of this protective nature of Tregs in response to chronic inflammation and its involvement in inducing liver fibrosis, cirrhosis, and hepatocellular carcinoma. We will also provide a detailed emphasis on the relevance of Tregs as an effective immunotherapeutic option for autoimmune diseases, liver transplantation, and chronic liver diseases including liver cancer.